Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

$\displaystyle\int{t^2}{{\sqrt[3]{t^3-1}}}\,dt$. Can someone give me a hint on how to solve this problem?

share|improve this question

closed as off-topic by Mike Miller, Sanath Devalapurkar, Hans Engler, Michael Albanese, T. Bongers Jun 10 at 2:47

This question appears to be off-topic. The users who voted to close gave this specific reason:

  • "This question is missing context or other details: Please improve the question by providing additional context, which ideally includes your thoughts on the problem and any attempts you have made to solve it. This information helps others identify where you have difficulties and helps them write answers appropriate to your experience level." – Mike Miller, Sanath Devalapurkar, Hans Engler, Michael Albanese, T. Bongers
If this question can be reworded to fit the rules in the help center, please edit the question.

Substitution. Let $u=t^3-1$. –  André Nicolas Jun 10 at 0:09
add comment

3 Answers 3

up vote 3 down vote accepted

Substitute the following

  • $u=t^3-1$
  • $du=3t^2 \, dt \implies \frac{du}{3}= t^2 \, dt$

So that we may now perform the integration by $u$-substitution. \begin{align}\int t^2 \sqrt[3]{t^3-1} \, dt &= \int \sqrt[3]{t^3-1} \, \underbrace{t^2 \, dt}_{du/3}\\ &= \int \sqrt[3] u \, \frac{du}{3} \\ &=\frac 13 \int u^{\frac 13} \, du \\ &=\frac 13 \frac 34u^{\frac 43} +C \\ &=\frac 14(t^3-1)^{\frac 43} +C\end{align}

share|improve this answer
Do not provide the whole answer. Allow the OP to do some work. –  Sanath Devalapurkar Jun 10 at 0:19
This isn't a homework problem, or at least it doesn't have the (homework) tag on it. So I am free to provide the whole answer. –  glace Jun 10 at 0:19
Yes, but simple problems such as these usually are homework. –  Sanath Devalapurkar Jun 10 at 0:20
I'm a little confused on the $3/4$ part –  user124557 Jun 10 at 0:30
Anti-power rule: $$\int y^{\frac 13} \, du= \frac{y^{\frac 13 + 1}}{\frac 13 + 1} + C = \frac{y^{\frac 43}}{\frac 43} + C = \frac 34 u^{\frac 43} + C $$ –  glace Jun 10 at 0:31
add comment

The usual substitution is $u=t^3-1$. Alternately, let $u^3=t^3-1$. Then $3u^2\,du=3t^2\,dt$, so we want $\int u^3\,du$.

share|improve this answer
add comment

Let $u=t^3-1\implies du=3t^2dt$. Hence, $$\dfrac{1}{3}\int \sqrt[3]{t^3-1}(3t^2dt)=\dfrac{1}{3}\int \sqrt[3]{u}du$$ You should be able to do this.

share|improve this answer
add comment

Not the answer you're looking for? Browse other questions tagged or ask your own question.